Separation of Rye Secalins by A-Page - Petrovičová, Lenka; Balážová, Želmíra; Vivodík, Martin; Gálová, Zdenka (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The aim of our study was to evaluate the electrophoretic profiles of secalins of fifteen genotypes of rye (Secale cereale L.), which were obtained by polyacrylamide gel electrophoresis in the presence at pH 3.1 (A-PAGE). Electrophoretic separation of storage proteins was conducted according to the methodology recommended by an international organization ISTA, with some own modifications. Fractions from the preparative separation were pooled in such a way that no components from one pool were present in the others. Doc-It LS software was used to detect and to calculate variability of genotypes within individual rye species.Preparative electrophoresis at low pH allowed a simple separation of γ75k-secalins, ω-secalins and γ40k-secalins from the crude material under non-denaturing conditions. The content of γ75k-secalins varied in analyzed collection of rye from 22.86% (variety Čerkascanka tetra) to 53.93% (genotype Valticke) with an average 39.27%. The proportion of ω-secalins in our samples was in an average 39.27%. The largest percent representation of ω-secalins was proved in variety Česke (58.68%) and the lowest part of this subunits was detected in variety Radomske (25.83%). Our results showed that average representation of γ40k-secalins was 22.05%, with the highest content in variety Vigľašske (32.44%) overleaf with the lowest part of this fraction was detected in Valticke (8.28%). The variety of wheat Chinese spring and Marquis were used as standards. Storage proteins consist of three fractions, which are the main part of grain proteins and are used as a marker not only for genetic variability investigation, but also for characterization of genotypes. These pooled fractions could be used as starting material for single polypeptide purification.